2007
DOI: 10.1063/1.2761886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of time-dependent density functional schemes for computing the oscillator strengths of benzene, phenol, aniline, and fluorobenzene

Abstract: In present study the relevance of using the time-dependent density functional theory (DFT) within the adiabatic approximation for computing oscillator strengths (f) is assessed using different LDA, GGA, and hybrid exchange-correlation (XC) functionals. In particular, we focus on the lowest-energy valence excitations, dominating the UV/visible absorption spectra and originating from benzenelike HOMO(pi)-->LUMO(pi(*)) transitions, of several aromatic molecules: benzene, phenol, aniline, and fluorobenzene. The TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 98 publications
8
90
0
Order By: Relevance
“…There are only a few studies that assess the reliability of theoretical oscillator strengths, for example, that of ref. [76]. In that study, it was found that the oscillator strengths from TDDFT depend strongly on the choice of the XC functional.…”
Section: Theoretical Methods For Excited Statesmentioning
confidence: 94%
“…There are only a few studies that assess the reliability of theoretical oscillator strengths, for example, that of ref. [76]. In that study, it was found that the oscillator strengths from TDDFT depend strongly on the choice of the XC functional.…”
Section: Theoretical Methods For Excited Statesmentioning
confidence: 94%
“…[89,94] Adiabatic time-dependent density functional theory (TD-DFT) [170,171] in the Kohn-Sham (KS) form is currently the method of choice for calculating the excited-state structure of large molecular systems. [172][173][174][175][176][177][178] Recently TD-DFT extensions for the calculations of molecular nonlinear optical properties have been suggested based on the residues of the quadratic response functions for TPA, [179,180] and on the quasi-particle formalism of the TD-KS equations for arbitrary frequency-dependent nonlinear optical polarizabilities. [181,182] Subsequently, the former approach was used for detailed studies of nonlinear polarizabilities in small organic molecules [183][184][185][186][187][188][189][190][191] and the latter method was applied to calculate OPA and TPA responses of several families of donor/acceptor sub-stituted conjugated organic chromophores [192][193][194][195][196][197] and various substituted branched structures.…”
Section: Introductionmentioning
confidence: 99%
“…28 In studies of lowest energy valence excitations of several aromatic molecules using time-dependent DFT, BHandHLYP functional was found to provide oscillator strengths values in good agreement with highly correlated CCSD data or reported high-quality experimental results. 34 Some tests even claimed that BHandHLYP was the only hybrid DFT method that successfully described the potential energy surface obtained with the CCSD(T) calculation 35 and gave reliable excitation energies for the p-p charge-transfer complexes. 29 The question regarding the best DFT method for amino acids and related systems remains unanswered as the amino acid systems are characteristically different from the systems tested before.…”
Section: Introductionmentioning
confidence: 99%